EVALUATION OF HEAVY METALS' CONCENTRATION AND PHYSICOCHEMICAL PARAMETERS OF GROUNDWATER WITHIN JOS METROPOLIS OF PLATEAU STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
This paper studied the quality of drinking water from borehole sources in Jos and its environs. The level of heavy metal concentrations and some physicochemical parameters were determined using standard methods. The result of heavy metal concentrations analyzed within the ten (10) sampling points shows that JS1 sampling point had a significantly high (p
Keywords: Heavy metals; Boreholes; Physicochemical; WHO